(untitled) (SAARC Journal of Agriculture, 2017)
The fatty acid, amino acid and fat soluble vitamin content of magur (Clarias batrachus) and singhi (Heteropneustes fossilis) were assayed from collected samples from different geographical locations. Length and weight of collected samples were (50-235g and 165-300 mm) for magur and (50-210g and 190-255mm) for singhi. The essential amino acid (EAA) and the non-essential amino acid (NEAA) content in magur and singhi did not differ significantly. The Vitamin A and D contents were significantly (P<0.05) higher in magur when compared to singhi. The Vitamin K content was significantly (P<0.05) higher in singhi compared to magur. Monounsaturated fatty acid (MUFA) content was 38.34±4.62 and 49.69±7.82 in magur and singhi respectively. Among the MUFA, oleic acid was significantly (P<0.05) higher in singhi. Palmitic acid was significantly (P<0.05) higher in magur than singhi. The PUFA content were 25.52±1.40 and 13.86±0.64 in magur and singhi respectively. The eicosapentanoic acid (EPA) and docosahexaenoic acid (DHA) content were 2.98±1.00 and 3.60±1.11; 2.25±0.86 and 1.60±1.09 respectively in magur and singhi. The ?3:?6 ratio in magur was 0.45:1 and in singhi 0.82:1. Both the catfishes were found to be nutrient rich with amino acid, fatty acid and vitamin. SAARC J. Agri., 14(2): 189-199 (2016)